Adsorption and removal studies of cadmium ion onto sulphonic/phosphonic acid functionalization resins. (4th May 2022) - Elfeghe, Salem; Anwar, Shams; Zhang, Yahui
Abstract: Cadmium is a persistent bio‐accumulative toxic metallic element, which causes hazardous impacts on living species, water, and the environment. This paper presents the study of cadmium ion removal from aqueous solutions in batch experiments using 22 ion exchange resins with different functional groups. It was found that Dowex G‐26 resin with a sulphonic functional group and Puromet™ MTS9570 resin with sulphonic and phosphonic functional groups had excellent performance for Cd (II) ion removal. The effects of resin dosage, adsorption time, initial concentration of cadmium, and initial pH of solution on cadmium removal were investigated systematically using Dowex G‐26 and Puromet™ MTS9570 resins. Maximum cadmium removal rates of 99.2% and 98.9% were achieved for G‐26 and MTS9570, respectively, at an initial cadmium concentration of 1000 mg/L, an initial solution pH of 5.0, an adsorption time of 30 min, and a 0.01 mg/L resin dosage for G‐26, and a 0.025 mg/L resin dosage for MTS9570. The ion‐exchange adsorption process was fast, and it reached equilibrium after 30 min of adsorption. The results obtained show that both resins performed well for the removal of Cd (II) ions from weakly acidic solutions. Langmuir, Freundlich, and Temkin isotherms models were employed to investigate and understand the adsorption characteristics. The results showed that the studied adsorption processes fitted well to the Langmuir adsorption isotherm. From the Langmuir adsorption isotherm, the maximum adsorption capacities of Cd (II) were found to be 78.125 and 51.020 mg/g for G‐26 and MTS9570, respectively. This research provides an efficient systemic approach for cadmium ion removal from aqueous solutions.